Respuesta :

Lenvy

Answer:

[tex]\left(2x-3\right)^2[/tex]

Step-by-step explanation:

[tex]4x^2-12x+9[/tex]

[tex]\mathrm{Rewrite\:in\:the\:form\:of}\:a^2+2ab+b^2:[/tex]

[tex]4x^2=(2x)^2[/tex]

[tex]9=3^2[/tex]

[tex]-12x=-2\cdot 2x\cdot 3[/tex]

[tex]=\left(2x\right)^2-2\cdot \:2x\cdot \:3+3^2[/tex]

[tex]\mathrm{Apply\:Perfect\:Square\:Formula}:\quad \:a^2-2ab+b^2=\left(a-b\right)^2[/tex]

[tex]\left(2x\right)^2-2\cdot \:2x\cdot \:3+3^2=\left(2x-3\right)^2[/tex]

[tex]=\left(2x-3\right)^2[/tex]

~Learn with Lenvy~

[tex]\\ \rm\Rrightarrow 4x^2-12x+9[/tex]

[tex]\\ \rm\Rrightarrow (2x)^2-2(2x)(3)+3^2[/tex]

So

  • (a-b)²=a²-2ab+b²

[tex]\\ \rm\Rrightarrow (2x-3)^2[/tex]

[tex]\\ \rm\Rrightarrow (2x-3)(2x-3)[/tex]